Prediction of Video Defect Rate Analysis Tool using Object Quality Metrics - M. Praneesh (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Video Analysis ensures quality of the video. The quality is directly correlated with video components. The video quality analysis has been performed with the help of quality features. Video Quality Assessment (VQA) algorithms are succeeding in as-sessing quality as a function of content which expects develop-ments in that direction. The Feature based approaches are faster than the pixel based approaches. The work extracts edges from test video using canny edge detection algorithm for finding falsy edges and the edge difference. The work also focused on software defect density measure on video quality analysis to find defect density in the test video. The proposed Video Defect Rate Analysis Tool (VDRAT) estimates the defects analyzed by the comparison of original and distorted video frames. The frames are taken as inputs and detects original and reference frame to predict quality of the entire video and validation has been done by objective testing me-thod..